Research progress in intracranial artery dissections over past 25 years: a review and bibliometric analysis - Zixuan Zhou; Zixuan Zhou; Zixuan Zhou; Bingyang Qin; Yang Chen; Yang Chen; Yang Chen; Ren Li; Ren Li; Ren Li; Biao Yang; Biao Yang; et al. (Frontiers in Neurology)
BackgroundA bibliometric and visual analysis of articles related to intracranial artery dissection (IAD) was performed to reveal the academic developments in this research field, to better assist researchers in reviewing previous research results, exploring current scientific research hotspots and cutting-edge trends, and obtaining a global perspective on IAD research.MethodsArticles on IAD published from January 1, 2000 to March 15, 2025 were searched, screened, and downloaded using the Web of Science Core Collection (WoSCC). All literature included in the study was analyzed using VOSviewer, CiteSpace and Microsoft Excel.ResultsA total of 1,130 articles were included in the bibliometric analysis from January 2000 to March 2025, with a general upward trend in the number of articles published each year, peaking in 2019 for annual publications. Collaboration network analysis showed that the United States, Japan, and Germany are the more influential countries in the field, with high numbers of published articles, citations, and collaborations with other countries. The journal with the most publications was World Neurosurgery. Lawton MT was the most active author with a cumulative total of 13 articles, while Biller J received the highest number of citations with a cumulative total of 1,033. Keyword analysis of the literature showed that “recanalization “reached the highest intensity of outbreaks, while “thrombectomy “,” outcome “, “risk “, and “diagnosis “showed an increase in citations in 2025, indicating that these subjects continue to be of significant interest.ConclusionThis study explores the evolving research trends and challenges in the area of IAD, presenting a thorough examination of both its historical and current research contexts. It offers valuable direction for future scholarly pursuits. By engaging in comprehensive research and examining various perspectives within the IAD domain, new insights can be uncovered, ultimately facilitating precise diagnosis and effective treatment of the condition.